- #1

- 220

- 0

## Main Question or Discussion Point

How do you find the limit to:

Lim

x->0+ sqrtx/(1-cosx)

I use the L'Hopital rule and i get

lim

x->0+ 1/(2sqrtx*sinx)

and I can't get anywhere after this. I even tried multiplying by sqrtx/sqrtx to get rid of the sqrtx at the beginning, but it still doesn't work. Please help, thanks.

Lim

x->0+ sqrtx/(1-cosx)

I use the L'Hopital rule and i get

lim

x->0+ 1/(2sqrtx*sinx)

and I can't get anywhere after this. I even tried multiplying by sqrtx/sqrtx to get rid of the sqrtx at the beginning, but it still doesn't work. Please help, thanks.